50 Clinical indications for trans-thoracic echocardiography. (30th September 2020) - O'Riordan, F; Hart, C; O'Flynn, AM; Hickey, Anne
Abstract : Background: Trans-thoracic echocardiography (TTE) is a commonly performed non-invasive investigation for the assessment of ventricular function and cardiac morphology. The British Society of Echocardiography have established guidance outlining twelve clinical indications in which echocardiography may provide incremental value to patient management (BSE Guidance). Aims: The aim of this study was to audit TTE requests received by the Cardiology Department and compare them against BSE Guidance. Our overall aim is to promote appropriate resource utilisation. Methods: We retrospectively collected all TTE requests received by the Cardiology Department over a four week period from August 2019 to September 2019. We examined the clinical indications for ordering a TTE and used BSE Guidance to classify the indications as appropriate, inappropriate, or unclear. Results: Thirty-two requests for TTE were received over the study period. The median patient age was 74 years [range 32–93 years]. Just over half of the patients 17/32 (52%) were male. The most common indications for TTE were to evaluate valvular pathology 11/32 (34%); either initial assessment 5/32 (16%) or surveillance of known valvular disease 6/32 (18%). The second most common indication was to assess cardiomyopathy 8/32 (25%), followed by evaluation of arrhythmias, palpitations or syncope 4/32 (13%). When compared with BSE Guidance, 18 (56%) requests were appropriate and 11 (34%) were inappropriate. Three (9%) requests were deemed unclear due to the lack of information contained in the request. Conclusion: An almost equal number of females and males were referred for TTE. The median age reflects the older cohort of patients at our hospital. Valvular pathology; either for diagnostic assessment or repeat evaluation was the most common indication for echocardiography, More than one-third of TTE requests received were not clinically indicated and combined with unclear requests, this amounted to more than 40% of requests. We would recommend implementation of BSE Guidance at our hospital to provide guidance for physicians making requests and ensure appropriate utilisation of limited resources for clinically indicated echocardiograms.